Degradation of atrazine by UV/chlorine: Efficiency, influencing factors, and products. (1st March 2016) - Kong, Xiujuan; Jiang, Jin; Ma, Jun; Yang, Yi; Liu, Weili; Liu, Yulei
Abstract: In this work, the degradation of atrazine by the combination of UV and chlorine (UV/chlorine) due to the formation of radicals during chlorine photolysis was systematically investigated in terms of efficiency, factors that influence the degradation kinetics, as well as oxidation products. It was found that the degradation efficiency of atrazine was enhanced by UV/chlorine compared to UV or chlorine alone. The degradation efficiency of atrazine was favorable at a lower pH, but was inhibited in the presence of natural organic matters. Meanwhile, the initial chlorine dosage, alkalinity, and chloride barely influenced the degradation efficiency under neutral pH conditions. The degradation of atrazine by UV/chlorine was inhibited in real waters (i.e., surface water and ground water) compared to in deionized water but was still more effective than UV alone. The oxidation products of atrazine resulting from de-alkylation, dechlorination-hydroxylation, alkylic-hydroxylation, alkylic-oxidation, alkylic-hydroxylation-dehydration, deamination-hydroxylation, and dechlorination-hydrogenation in UV/chlorine process were detected, which were slightly different from those formed in UV/H2 O2 (commonly used UV-based advanced oxidation process). Particularly, the yields of three primary transformation products (desethyl-atrazine (DEA), desisopropyl–atrazine (DIA), and desethyl–desisopropyl–atrazine (DEIA)) were comparatively quantified in these two processes. The different trend of them formed in UV/chlorine system (DEA:DIA≈4) compared to that formed in UV/H2 O2 system (DEA:DIA≈1) could be ascribed to the different reaction reactivities and mechanisms between HO and Cl with atrazine. Graphical abstract: Highlights: Atrazine can be efficiently degraded by UV/chlorine compared to UV alone. The degradation efficiency of atrazine in UV/chlorine is inhibited by NOM. The degradation of atrazine by UV/chlorine is favorable at acidic pH. The formation of primary products in UV/chlorine is different from that in UV/H2 O2 .